Investigation of Effects of Some Schiff Bases on Behaviour of Mild Steel in Acidic Medium - Kahyaoglu, H.; Tuncel, M. (Asian Journal of Chemistry, 2014)
This study investigated the effects on the behaviour of mild steel in 0.1 M HCl and 0.1M H2SO4 solution of the [4-(3-methoxy-salicylideneamino)-5-hydroxynaphthalene-2,7-disulfonic acid diisodium salt (L1) and 4-(3-methoxysalicyaldimino)-5-hydroxy-6-(2-nitrophenylazo)-2,7-naphthalene disulfonic acid disodium salt (L2) in different concentrations with current-potential and electrochemical impedance spectroscopy (EIS) techniques. Polarization curves revealed that Schiff bases are mixed type inhibitors. Adsorption of Schiff bases on mild steel surface is spontaneous and obeys Langmuir's isotherm. As a result, the inhibition efficiency of L2 is higher than L1 for the studied medium. Moreover, inhibition efficiency increases with increase in the concentration of the inhibitor.